Variations in upper limb and trunk muscles activation during isometric exercises with or without exertion of control - Murofushi, Koji; Yamaguchi, Daisuke; Hirohata, Kenji; Furuya, Hidetaka; Mitomo, Sho (Isokinetics and exercise science, 2022)
BACKGROUND: Muscle activation during isometric contraction can be changed using an external-focus instruction method. OBJECTIVE: To explore and compare the activity of eight upper limb and trunk muscles during isometric chest squeeze exercises, performed in the same posture with and without the exertion of control to avoid crushing an object. METHODS: Muscle activation by an isometric chest squeeze with 45 ∘ shoulder abduction and forearm pronation was examined. Isometric chest squeeze exercises were performed while holding objects with maximum pressure, and with exerted control to avoid crushing the object Muscle activation was measured by surface electromyography. RESULTS: During the exercises performed while exerting control to avoid crushing the object the lower trapezius ( p < 0.001) and latissimus dorsi ( p = 0.03) showed significantly higher activity. During the exercises performed without control, the upper trapezius, serratus anterior, and pectoralis major showed significantly higher activity ( p = 0.016, p < 0.001, p < 0.001, respectively). CONCLUSIONS: This novel isometric exercise can increase the scapular muscles in the intermediate range of the glenohumeral joint. Therefore, it may assist in improving sport performance, in preventing injuries and in rehabilitation following musculoskeletal injuries.